Namasangiti Practices and Cultural Cohesion in Chilancho Caitya - Gopal Prasad Sigdel,; Shrestha, Bidhya; Roji KC,; Roji Kansakar,; Shrestha, Tara Lal (Journal of Business and Social Sciences, 2025)
This study based on descriptive mixed-method explores how Namasangiti being practiced persists for a long period of time supportive to cultural cohesion. Employing insights from ethnographic observations, key informant interviews, interactions, and desk reviews, this study firstly examines the collective practices of Namasangiti in Chilancho Caitya Kirtipur, concerning how it stands as a profound microcosm of unity for diversity on spatial, philosophical, and generational level. It also analyses how the philosophy of Namasangiti and its ritualistic practices connect community. The Aryamanjusrinamasaṃgiti roots out as a core Mahayana and Vajrayana texts venerating the bodhisattva Manjusri within the same community but across different spatial and institutional contexts. It highlights three central inquiries and examines the collective practices in liturgical rhythm, participation, and community engagement. Meanwhile, it investigates how the underlying philosophy of Namasangiti fosters cultural cohesion with ethical relations through embodied practice. Finally, the study further show findings how the philosophy of Namasangiti itself acting as a powerful connective flavor from generation to generation as seen at Chilancho Caitya.